Fingerprint verification system - Adano, Vaughn Garret O. (2003)
Fingerprint verification system is considered to be one of the most reliable in terms of addressing the problem of identifying people. This is due to the fact that fingerprints are considered to be unique in every individual. The two ways in conducting fingerprint verification are manually and automatically. Manual fingerprint verification, however, is very tedious, time-consuming and expensive that it is incapable of meeting the speed and reliability requirements of today's systems. As a result, the demand for automatic fingerprint identification systems (AFIS) is rapidly increasing. This type of system is now widely used in forensic and other applications such as identifying criminals, login systems, access controls, and even ATM card verification. This paper describes the design and implementation of a real-time automated fingerprint verification system operating in two stages: minutia extraction and minutia matching. A hybrid algorithm from the methods proposed by Ratha et.al and Maio and Maltoni is implemented for extracting features from an input fingerprint image. For minutia matching, we used a hybrid fingerprint matching scheme that uses both minutiae and ridge flow information to represent and match fingerprints. A set of Gabor Filtered images, whose square tessellations are used to construct a 4-dimensional feature map called the ridge feature map, is used along with the minutiae set of a fingerprint image for our matching purposes. The system has been tested on 70 fingerprint images from NIST Database. Our current system does not outperform existing verification methods. However, by combining the algorithms used by the most successful systems, we have been able to develop a system with an acceptable verification accuracy.